2023
DOI: 10.1039/d3ta06163a
|View full text |Cite
|
Sign up to set email alerts
|

Lithium metal batteries with in situ copolymerized fluorinated polyether electrolytes

Zhichun Chen,
Ji Xian,
Xiaobo Pan
et al.

Abstract: Ether electrolytes are an important component of lithium metal batteries. However, the safety hazards of liquid solvent leakage and combustion, as well as the relatively narrow electrochemical stabilization window are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…32−34 Particularly, poly(1,3-dioxolane) (PDOL) obtained via simple ring-opening polymerization of 1,3-dioxolane (DOL) does not need the injection of additional initiators, thus gaining more concerns. 35,36 Also, the flexible organic layer formed by DOL polymerization contributes to accommodate the rapid volume change in Li electrode cycling. 37−39 Inspired by the simple fabrication of in situ PDOL and the flexible PDOL-filled feature, 40 we herein adopt an in situ polymerization strategy to construct double-stabilized PDOL interface layers between PAN-containing SN and LLZTO and cathode/anode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32−34 Particularly, poly(1,3-dioxolane) (PDOL) obtained via simple ring-opening polymerization of 1,3-dioxolane (DOL) does not need the injection of additional initiators, thus gaining more concerns. 35,36 Also, the flexible organic layer formed by DOL polymerization contributes to accommodate the rapid volume change in Li electrode cycling. 37−39 Inspired by the simple fabrication of in situ PDOL and the flexible PDOL-filled feature, 40 we herein adopt an in situ polymerization strategy to construct double-stabilized PDOL interface layers between PAN-containing SN and LLZTO and cathode/anode.…”
Section: Introductionmentioning
confidence: 99%
“…In situ polymerization is a promising strategy for achieving low interfacial resistance and high ion conductivity. It has been demonstrated that in situ processed polymers including poly­(methyl methacrylate) (PMMA), poly­(vinylene carbonate) (PVC), poly­(tetrahydrofuran) (PTHF), and poly­(1,3-dioxolane) (PDOL) can fill the gaps between electrolytes and electrodes, thus achieving a tight interfacial contact. Particularly, poly­(1,3-dioxolane) (PDOL) obtained via simple ring-opening polymerization of 1,3-dioxolane (DOL) does not need the injection of additional initiators, thus gaining more concerns. , Also, the flexible organic layer formed by DOL polymerization contributes to accommodate the rapid volume change in Li electrode cycling. Inspired by the simple fabrication of in situ PDOL and the flexible PDOL-filled feature, we herein adopt an in situ polymerization strategy to construct double-stabilized PDOL interface layers between PAN-containing SN and LLZTO and cathode/anode. Such fabricated composite electrolytes are demonstrated to greatly suppress the passivation reaction of PAN/Li and simultaneously guarantee Li + migration, finally realizing superior battery performance.…”
Section: Introductionmentioning
confidence: 99%